The role of Quality of work of life and Organizational Citizenship behavior in mediating the influence of workload on the performance of employees of the PUPR Service of Central Maluku - Ratihsabella, Inesa Nining; Wahyuni, Purbudi; Ambarwati, Sri Dwi (Strata International Journal of Social Issues, 2025)
This study investigates the mediating roles of Quality of Work Life (QWL) and Organizational Citizenship Behavior (OCB) in the relationship between workload and employee performance within the Public Works and Spatial Planning Office (PUPR) of Central Maluku Regency. Amid fluctuating employee performance from 2020 to 2024, organizational factors such as work environment and collaborative culture have emerged as potential determinants of employee outcomes. Using a quantitative approach, data were collected from 80 civil servants through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that workload significantly influences employee performance, with QWL acting as a significant mediator in this relationship. However, OCB does not significantly mediate the effect of workload on performance. These findings highlight the importance of enhancing QWL through supportive workplace policies to sustain employee performance under demanding workloads. This study contributes to public sector human resource management literature and offers practical insights for improving civil servant effectiveness through balanced workload management and workplace quality enhancement.